2007
DOI: 10.1016/j.toxicon.2007.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of crude and partially purified extracts of marine Synechocystis and Synechococcus cyanobacterial strains in marine invertebrates

Abstract: Among the Cyanoprokaryota, the genera Synechocystis and Synechococcus have rarely been studied with respect to potential toxicity. This is particularly true with marine environments where studies about the toxicity of cyanobacteria are restricted to filamentous forms at the warmer temperate and tropical regions and also to filamentous forms at cold seas such as the Baltic Sea. In this study, we describe the effects of cyanobacterial strains of the Synechocystis and Synechococcus genera isolated from the marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 38 publications
(38 reference statements)
3
41
2
2
Order By: Relevance
“…For all the extracts and concentrations, significant differences were found (p < 0.05) from the control, excluding the pairs with concentrations of 1.6-3.2 mg mL -1 and 3.2-6.3 mg mL -1 of LEGE 07083 aqueous extract (p = 0.354 and 0.787, respectively). The results are in agreement with the results of Martins et al [11] that also observed anomalies at the larval stage and inhibition of the embryogenesis exposed to marine cyanobacterial extracts, although the isolates now studied are from estuarine habitats. Our data demonstrate the presence of compounds in the extracts that can interfere with growth factors, as observed in previous studies [15].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For all the extracts and concentrations, significant differences were found (p < 0.05) from the control, excluding the pairs with concentrations of 1.6-3.2 mg mL -1 and 3.2-6.3 mg mL -1 of LEGE 07083 aqueous extract (p = 0.354 and 0.787, respectively). The results are in agreement with the results of Martins et al [11] that also observed anomalies at the larval stage and inhibition of the embryogenesis exposed to marine cyanobacterial extracts, although the isolates now studied are from estuarine habitats. Our data demonstrate the presence of compounds in the extracts that can interfere with growth factors, as observed in previous studies [15].…”
Section: Resultssupporting
confidence: 92%
“…Even still, one of 18 methanolic extracts, LEGE 06071, induced acute effects on the A. salina nauplii with a LC 50 of 17.81 mg mL -1 (95% confidence interval of 11.63 to 27.30 mg mL -1 ). It was also observed that the LC 50 values calculated were more prominent at 48 h, which confirms the sensitivity of nauplii observed in previous works [3,8], suggesting that toxicity is much higher after 48 h exposure than after 24 h. Moreover, previous work showed that the crude extracts of marine Synechocystis strains reduced the survival of A. salina nauplii similarly to the results obtained here [11]. The most toxic extracts in this work were those of the filamentous forms Leptolyngbya and Microcoleus.…”
Section: Resultssupporting
confidence: 91%
“…Some genera described by [2] were not found in our study (Chamaecalyx, Dermocarpella, Entophysalis, Hydrococcus, Trichocoleus, Porphyrosiphon,Siroc oleum, and Spirocoleus), whereas Xenococcus, Microcoleus, Spirulina morphotypes were present in our field samples but its isolation was not successful. On the other hand, genera that are not described by these authors were present in our samples (Aphanothece, Cyanobium, Synechocystis, Chroococcidiopsis,Chroococcopsis, Leptolyngbya, Pseudanabaena, Romeria, Schizothrix, Nostoc, and Scytonema), some of them also confirmed by a recent studies on the Portuguese coast: Synechocystis, Cyanobium, andLeptolyngbya [9] and [26]. However, Araújo et al [2] based their work not only on new records but also on literature references and herbarium data, and did not isolate the observed specimens.…”
Section: Morphological Characterizationsupporting
confidence: 90%
“…Martins et al. [26] demonstrated that extracts of marine Synechocystis and Synechococcus strains isolated from the Portuguese coast were toxic to marine invertebrates possibly implicating the presence of other toxic compounds.…”
Section: Dna Sequence and Phylogenetic Analysismentioning
confidence: 99%
“…Magalhães et al (2003) reported that S. aquatilis produced microcystin in Sepetiba Bay, Brazil, where were observed regular blooms of these cyanobacteria, and the microcystin was found in fish caught in this bay. Several works of Martins, Pereira, Welker, Fastner, and Vasconcelos (2005), Martins, Fernandez, Beiras, and Vasconcelos (2007) and Martins et al (2008) reported the production of microcystin by the marine cyanobacteria, including genus Synechocystis. Vareli et al (2012) reported the presence of the hepatotoxic microcystins in the Mediterranean Sea, and he suggested a potential association of microcystins with Synechococcus and/or Synechocystis cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%